IMPLEMENTASI MERDEKA BELAJAR MELALUI PROGRAM KAMPUS MENGAJAR DALAM MENINGKATKAN KOMPETENSI LITERASI DAN NUMERASI - Azzahra Safira Sekar Putri; Adriani Rianita Putri; Kaisha Az Zahra Muchtar; Neng Ilma; Neng Sonia; Siti Ainun Mahpulah; Yuggo Afrianto (JPMUJ, 2024)
The Teaching Campus Program Batch 2 is one of the programs from the Merdeka Campus (MBKM) which is a teaching assistant to empower students from all over Indonesia in helping the learning process, creating creativity to improve the quality of learning in elementary schools throughout Indonesia, especially those in the 3T area and accreditation C. The objectives of the Teaching Campus include increasing the ability or competence of students, especially in terms of literacy and numeracy, assisting in technology adaptation, school administration, as well as improving student character and increasing interest in learning during the COVID-19 pandemic. The results show that this program is proven to have a positive impact on students such as interest in learning, literacy skills, and numeracy. In addition, the adaptation of technology and school administration is also going well, this is proven by changes for the better during the activities.